Ability Locus of Control in Mediating Islamic Attitude and Knowledge on Financial Behavior - Solihatun Nisak; Rahmat Agus Santoso (EKUILIBRIUM : JURNAL ILMIAH BIDANG ILMU EKONOMI, 2023)
The primary objective of this study was conducted (1) to test the influence of financial knowledge and locus of control on financial behavior, (2) to find the impact of Islamic financial attitudes toward financial conduct and Locus of Control, (3) to investigate influence the role of locus of control as a mediator between financial knowledge and Islamic finance attitudes in relation to financial behavior. Although the model concept used in this study has been explored previously, the specific indicators for the Islamic financial attitude variable have not been studied before.This research follows an explanatory approach, which involves testing hypotheses to understand the relationships between variables. The study included a sample of 130 Muslim farmers from Tuban Regency, selected through cluster sampling. Data analysis was conducted using SmartPLS3 software, employing Path Analysis as the analytical technique.Based on the data analysis and inquiry results, the study found that Islamic financial attitudes had a positive impact on individuals' financial locus of control and financial behavior. However, financial knowledge did not significantly affect financial locus of control and behavior.Furthermore, the locus of control was identified as a mediator between Islamic financial attitudes and individuals' financial behavior, indicating that it played a role in influencing financial behavior based on their attitudes towards Islamic finance. However, the locus of control was not capable of mediating the impact of financial knowledge on financial behavior.